Feed the startup beast : a 7-step guide to big, hairy, outrageous sales growth - Williams, Drew, 1959- (McGraw-Hill Education, 2013)
Whether you're wondering how to get your startup off the ground or looking for answers to why your business has stalled; this groundbreaking guide will show you how to feed - and unleash - the beast that is your business. --